Preparation and optimization of self-organized ti02 nanotubes formation by anodic Oxidation / Zafirah Usaili - Usaili, Zafirah (2015)
The main focus of this research is to synthesize and to optimize the properties of TiCh nanotube with its final applications as photocatalyst for degradation of dye water. The growth mechanism of self-organized TiCh nanotube formation that were prepared by anodization of Ti foil in an electrolyte containing F* ions were also proposed in this work.Various parameters were conducted and analyzed. These included the different voltage, different anodization time, different pH, different electrolytes, and different annealing temperature. Since the morphological and structural properties were the main data that needed in order to understand the mechanism of TiCh nanotube formations,therefore several characterization technique were used such as field emission scanning electron microscope (FESEM) with EDX for morphological and elemental studies, X-ray diffraction spectrometer (XRD) for structural and phase identification, and UV-VIS for optical study. The optimum parameters were finally gathered with well-organized and uniform distribution of TiC>2 nanotubes which were formed at 19 V for 30 min in pH 3 electrolyte which contained 0.7g NH4F and 100 ml NaSC>4. FESEM results, showed that the diameter of nanotubes changed directly proportional to the parameter control. For example as the voltage increased the diameter were increased. In here, the smallest diameter achieved was at 30 nm and the biggest diameter achieved was at 100 nm. The length of Ti02 nanotube were also changed and the highest length achieved was at 500 nm. However, FESEM images clearly shown that nanotubes were hollow in shape with mouth opening at the top end and closed at the bottom of the tubes. The EDX analysis showed that Ti, and O, elements were existed in the sample. Thus proved that TiC>2 nanotube were occurred. The XRD results showed that, for pure Ti foil and as-anodized sample only appeared strong peak of Ti and weak amorphous peak of TiC>2. However, the crystalline sharp peak were appeared at 400 °C to 800 °C. Whereby, the phase was transformed from anatase to mixture of anatase and rutile from at 500 °C. The TiCh nanotubes had shown a good result in photocatalytic activity under degradation of mixture of anatase and rutile (500 °C) at 19 V and pH 3 within 1 hour of methyl red degradation. TiCh nanotubes with thinner walls and longer tubes have a more pronounced photocatalytic activity as compared with non-uniform thicker wall and longer. The schematic diagram and detail discussion on growth mechanism were explained in Chapter 4.